Upaya Kepala UPT SMP Negeri 18 Medan dalam Meningkatkan Mutu Lulusan melalui Pencapaian 8 (Delapan) Standar Nasional Pendidikan - Kusuma, Dewi Sri Indriati; Lubis, Wildansyah; Rahman, Arif; Joharis, M. (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2024)
This qualitative study examines the achievement of eight national education standards among state secondary schools in Medan. Data collection involved observation, documentation, and interviews with relevant informants. The research found that there were no significant differences between public and private schools in terms of content and process standards, with both meeting the required standards. However, differences were observed in graduate competency standards, educator and education personnel standards, facilities and infrastructure standards, asset management standards, lighting standards, and assessment standards. Specifically, graduate competency standards differed in terms of the specific characteristics of graduates, while educator and education personnel standards were primarily under the authority of the school principal. Facilities and infrastructure standards included procedures for acquisition, asset management standards were more flexible, lighting standards focused on the source of lighting, and assessment standards were well accommodated. Overall, this research provides valuable insights into the achievement of national education standards among state secondary schools in Medan.